Antioxidant and Inhibitory Capacity of Tomato Leaf Ethanolic Extract against Streptococcus mutans, Porphyromonas gingivalis, and Candida albicans - Mendoza, Yeiner; Arias-Londoño, Mónica; Sánchez-Garzón, Juliana; Rojas-Vahos, Diego Fernando; Robledo-Sierra, Jairo (Vitae, 2022)
Background: Tomato is a source of bioactive compounds, antimicrobials, and antioxidants. Tomato leaf preparations have been empirically used for anti-inflammatory, analgesic, antibiotic, and antiseptic purposes. However, research on the potential activity of tomato leaf extracts against oral microorganisms and in managing oropharyngeal infections is scarce. Objective: To investigate tomato leaf ethanolic extract’s antioxidant and growth inhibitory capacity against common oral pathogenic microorganisms, namely, Streptococcus mutans, Porphyromonas gingivalis, and Candida albicans. Methods: Ethanolic extracts were made from ‘Chonto’ tomato (Lycopersicon esculentum) leaves. The antimicrobial activity was measured with the microdilution technique using vancomycin and fluconazole as positive controls. The antioxidant capacity was measured with the ORAC assay using Trolox as a positive control. Results: We found a high percentage of growth inhibition (≥100%) against S. mutans and P. gingivalis at a concentration of 500 mg/L. However, the extract was ineffective in inhibiting the growth of C. albicans. Finally, we observed that the extract exerted a high antioxidant capacity (126%) compared to the positive control. Conclusions: This study provides new insights into the potential antimicrobial effect of tomato leaf extracts on common oral pathogenic bacteria, which may ultimately result in the development of new herbal products that might help prevent and treat oral infections, such as dental caries and periodontal disease. Our findings also support previous studies on the high antioxidant capacity of tomato leaf extracts.